Women in the boardroom: A comparison of gender diversity policy highlighting the role of context in Norway and the United Kingdom - Prescott, William (2022)
Gender diversity in leadership is improving and the discussion of women in the boardroom is generating traction globally. However, researchers have not reached a consensus upon the best way to increase diversity. The purpose of this dissertation is to attempt to assess the progress of both voluntary and compulsory legislative approaches to increase women in leadership. This will be achieved by a cross-country analysis of the progress and approaches used within Norway and the United Kingdom (UK). The objective is to assess if either of these approaches pose an exemplary policy for policy makers in other European nations and the United States.